(untitled) (Fiep Bulletin - online, 2011)
This article tells our supervised internship experience in the discipline of Physical Education. Our theme was social exclusion, which was shown and related to practical situations. We use as a competitive strategy games with its exclusive character and cooperative games as a comprehensive solution, to give a critical reflection of our students and similar practices before these and other situations in which social exclusion is present in our lives.